The Role of Civil Society Organizations in Strengthening Democratic Development in Iraq - مهدي, حنين كامل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Civil society is considered one of the fundamental pillars of building the modern state and consolidating democratic practices, as it plays a pivotal role in enhancing popular participation and reinforcing the principles of transparency, pluralism, and human rights. In Iraq, the urgent need for civil society organizations emerged after 2003, because of the political, security, and social transformations the country experienced, accompanied by the collapse of state institutions and the escalation of sectarian conflicts and communal strife. This study focuses on analyzing the role of civil society organizations in strengthening democratic consolidation in Iraq, by examining their emergence, mechanisms of activation, and the challenges they face, while also exploring their prospects as one of the key pillars of democratic transition.